1999
DOI: 10.1039/a905460j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structures and NMR and luminescence spectra of lanthanide complexes of 1,4,7,10-tetraazacyclododecane with N-methylene(phenyl)phosphinic acid pendant arms †

Abstract: Complexes of 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetrayltetramethylenetetrakis(phenylphosphinic acid) H 4 L 1 with yttrium and a number of lanthanides were synthesized and the crystal structures of Li[LaLThe complexes are isostructural with RSRS configurations at the phosphorus atoms. The ligand is co-ordinated by four nitrogen atoms in a plane and by four phosphinate oxygen atoms in a parallel plane. The planes form a twisted square prismatic co-ordination sphere. A molecule of water capping the O 4 plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…Taking into account also the luminescence measurements on europiA C H T U N G T R E N N U N G um-A C H T U N G T R E N N U N G (III) complexes of tetraphosphorus acid 1,4,7,10-tetraazacyclododecane (cyclen) derivatives in which a strong secondsphere hydration of the complexes was proven [18] and the precision of the above luminescence measurements, it can be concluded that the final product of Eu III complexation has no coordinated water molecule. It also agrees with the previous 17 O NMR spectroscopic measurements.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Taking into account also the luminescence measurements on europiA C H T U N G T R E N N U N G um-A C H T U N G T R E N N U N G (III) complexes of tetraphosphorus acid 1,4,7,10-tetraazacyclododecane (cyclen) derivatives in which a strong secondsphere hydration of the complexes was proven [18] and the precision of the above luminescence measurements, it can be concluded that the final product of Eu III complexation has no coordinated water molecule. It also agrees with the previous 17 O NMR spectroscopic measurements.…”
Section: Resultssupporting
confidence: 93%
“…[13,[16][17][18]21,22] Similarly, in the solid state, both SA and TSA structures were observed for the complexes of dota-like ligands [3,6,9] and only the TSA arrangement was found in the complexes of dotp and other tetraphosphorus derivatives. [13,[16][17][18]21,22] Dota complexes are nona-coordinated and have one water molecule capping the O 4 -plane, except for the TSA isomer of the Yb 3 + and Lu 3 + complexes, which have no inner-sphere water. [20a] In contrast, the coordinated water molecule is missing (except the largest lanthanideA C H T U N G T R E N N U N G (III) ions) in the complexes of tetraphosphorus ligands.…”
Section: A C H T U N G T R E N N U N G (Dotp)]mentioning
confidence: 95%
See 3 more Smart Citations